Islam in Europa of ‘Europese islam’: Sarajevo - Mieke van Dijk; Edien Bartels (Religie & Samenleving)
In order to contribute to the ongoing, often theoretical debate about Islam in Western Europe the study of actual European Muslim societies becomes relevant. The authors of this article chose to study the way Muslims in Bosnian Sarajevo, people who have been European from the outset and Muslims for centuries, think and behave in relation to several key-characteristics of European identity and society. From this study the researchers conclude that Muslims in Sarajevo have little trouble thriving in a modern and secular society in which headscarves, mixed marriages and ethnic plurality are self evidently integrated into daily life.